2014
DOI: 10.7755/fb.112.4.6
|View full text |Cite
|
Sign up to set email alerts
|

In cold blood: evidence of Pacific sleeper shark (Somniosus pacificus) predation on Steller sea lions (Eumetopias jubatus) in the Gulf of Alaska

Abstract: Abstract-Temperature data received post mortem in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…From these observations, the authors derived a 45-day postoperative survival study inclusion criterion. All 49 otariids had survival confirmed beyond the 45-day postoperative study inclusion criterion, whether released after one, two or up to eight weeks following surgery [49,57]. These studies also demonstrated that transmitter implantation has no detectable effect on postrelease movement and diving behavior as compared to animals that also underwent temporary captivity but without LHX tag implants [57].…”
Section: Life-long Implanted Vital Rate Transmitterssupporting
confidence: 49%
See 3 more Smart Citations
“…From these observations, the authors derived a 45-day postoperative survival study inclusion criterion. All 49 otariids had survival confirmed beyond the 45-day postoperative study inclusion criterion, whether released after one, two or up to eight weeks following surgery [49,57]. These studies also demonstrated that transmitter implantation has no detectable effect on postrelease movement and diving behavior as compared to animals that also underwent temporary captivity but without LHX tag implants [57].…”
Section: Life-long Implanted Vital Rate Transmitterssupporting
confidence: 49%
“…No differences in survival patterns between implanted animals and nonimplanted controls were detectable between the ages of 14 months to five years [65]. From the ratio of dual-to single-tag data returns in 20 mortalities detected to date (through 2016) and in 10 dual-tag carcass simulations, data return probability was estimated at >0.98 [49]. Of the 17 female Steller sea lions in that study implanted with single (n = 1 animal) or dual tags (n = 16 animals) between 2005 and 2014, eight animals have died by predation [49], and nine remain alive.…”
Section: Life-long Implanted Vital Rate Transmittersmentioning
confidence: 99%
See 2 more Smart Citations
“…The end-point of tracking data can reveal important information about the fate of that tracked animal. For example, bio-logging data in animals as diverse as raptors and eels can provide evidence that individuals have died [75,76] and so tags might therefore be able to assess mortality rates through space and time [77,78] as is commonly done for terrestrial species using tags equipped with mortality switches [79].…”
Section: Discussionmentioning
confidence: 99%